RETRACTED: Evaluation of post-COVID mortality risk in cases classified as severe acute respiratory syndrome in Brazil: a longitudinal study for medium and long term - Rodrigues, Nádia Cristina Pinheiro; Andrade, Mônica Kramer de Noronha (Frontiers in Medicine, 2024)
BackgroundThere are few studies in the literature evaluating post-COVID mortality in Brazil, along medium and long term, especially in those who presented severe clinical disease.ObjectiveThis study aims to investigate the factors associated with post-COVID mortality of severe acute respiratory syndrome (SARS) cases from 2020 to 2023 in Brazil, along medium and long term.MethodsRetrospective cohort study using notification data of SARS classified as COVID-19 from the Brazilian National Information System, “Sistema de Vigilância Epidemiológica (SIVEP),” during the period 2020 to 2023. Data included demographics, comorbidities, vaccination status, number of COVID-19 vaccine doses, city of residence, and survival outcomes. Classic Cox, Cox mixed effects, and Cox fragility models were used to assess medium and long-term risks of dying post-COVID.ResultsIn the medium and long-term periods studied, 5,157 deaths were recorded out of 15,147 reported SARS/COVID-19 cases. Of these deaths, 91.5% (N = 4,720) occurred within the first year, while 8,5% (N = 437) after the first year. People without formal education, the older adult, had higher percentages of deaths in both periods. In the medium-term post-COVID period, the risk of death was reduced by 8% for those who had been vaccinated while in the long-term post-COVID period, the risk of death almost doubled for those who had been vaccinated. While in the medium term, there was a reduction in mortality risk for those who took two or three doses, in the long term the risk of death was greater for those who took one or two doses.ConclusionThe protective effect of COVID-19 immunization was observed up to one year after the first symptoms. After one year, the effect was reversed, showing an increased risk of death for those vaccinated. These results highlight the need for further research to elucidate the factors that contribute to these findings.